2007
DOI: 10.1007/s11136-007-9260-y
|View full text |Cite
|
Sign up to set email alerts
|

Short-term physical and emotional health outcomes of public sector ART in the Free State province of South Africa

Abstract: The study suggests that the poorest of the poor are not the first beneficiaries of the public programme. Most importantly, the present findings demonstrate the positive physical and emotional health outcomes of the first 6 months of ART in the Free State, South Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 65 publications
(61 reference statements)
0
27
0
1
Order By: Relevance
“…The fifth EuroQoL item, measuring anxiety and depression, is used to measure the third component of SWB, the lack of unpleasant affect. This instrument has shown good reliability and construct validity in earlier studies of QoL among ART patients in South Africa (Wouters, Meulemans, van Rensburg, Mortelmans, & Heunis, 2007).…”
Section: Study Populationmentioning
confidence: 90%
“…The fifth EuroQoL item, measuring anxiety and depression, is used to measure the third component of SWB, the lack of unpleasant affect. This instrument has shown good reliability and construct validity in earlier studies of QoL among ART patients in South Africa (Wouters, Meulemans, van Rensburg, Mortelmans, & Heunis, 2007).…”
Section: Study Populationmentioning
confidence: 90%
“…They also reported energy and drive impairments in 75% and sleep impairments in 71% of the sample. Also using the ICF, van As et al [26] [32,33]. Two studies [32][33][34] reported improvements in the area of emotional functions, energy and drive while being on treatment; however, one study highlighted how activity limitations continued to affect the patient's life when on ART [33].…”
Section: Impairments Related To Body Structure and Functionmentioning
confidence: 99%
“…Similarly, Nair and Patel reported decreased physical functioning as measured by mobility. [32,33,[48][49][50] reported improvement in mobility upon initiating ART, with participants followed for the first 12 or 18 months. The study by Karbore et al [51] showed that among participants not receiving community services (i.e., food and homebased care), the mean physical functioning score increased by 1.6 points to 11.2 at 12 months but then decreased to 10.6 at 18 months, while the group which received community services improved continuously.…”
Section: Mobility (D4)mentioning
confidence: 99%
“…[1][2][3][4][5] Preliminary studies in sub-Saharan Africa provide evidence that public-sector ART programs are effective in delivering sustained improvements in patient well being, confirming universal treatment access as a key policy priority in these resource-limited settings. 6,7 However, there is no room for complacency because ART is a highly complex therapy requiring near-perfect and sustained adherence to remain effective.…”
Section: Introductionmentioning
confidence: 99%